Literature and the Encounter with God in Post-Reformation England - Martin, Michael, 1962 May 3- (Ashgate, 2014)
Each of the figures examined in this study -John Dee, John Donne, Sir Kenelm Digby, Henry and Thomas Vaughan, and Jane Lead -is concerned with the ways in which God can be approached or experienced. Michael Martin analyses the ways in which the encounter with God is figured among these early modern writers who inhabit the shared cultural space of poets and preachers, mystics and scientists.